HSecGR: Highly Secure Geographic Routing. (15th February 2017) - Boulaiche, Mehdi; Bouallouche-Medjkoune, Louiza
Abstract: An ad hoc wireless network is a set of nodes connected by wireless links in which nodes cooperate to forward packets from a source to a destination. Geographic routing (or position-based routing) has become an attractive solution for such networks since it reduces routing control overhead flooded in the network to construct routes (routes discovery). Many geographic routing protocols have been designed to guarantee packet delivery in such networks. However, these protocols consider that all nodes in the network are trustworthy which allows malicious nodes to violate network security and disrupt packet forwarding. In this paper, we propose and evaluate a new security approach that secures geographic routing protocols against a variety of attacks. Our approach is based on the use of MACs to allow intermediate nodes to verify the authenticity and the integrity of forwarded packets and uses authenticated acknowledgements to prevent packet dropping attacks. To meet node's resource constraints, we have based our solution on symmetric cryptography. Our solution is robust against modification and dropping attacks even in the presence of compromised nodes in the network.